2021
DOI: 10.3390/jcm10112349
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Recurrence and Graft Survival in Renal Transplant Recipients with a History of Pretransplant Malignancy: A Matched Pair Analysis

Abstract: Organ scarcity demands critical decision-making regarding eligible transplant candidates and graft allocation to ensure best benefit from renal transplantation (RTx). Among the controversial relative contraindications is a history of pretransplant malignancy (PTM). While oncological outcomes of PTM-RTx recipients are well described, data on graft-specific outcome are scarce. A retrospective double case control matched pair analysis (60 months follow-up) was carried out and RTx-recipients were stratified for hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…Also, the methods used for screening cancer development as well as social factors such as smoking, alcohol use, and family history could not be reported. Furthermore, there is a recent report that a pretransplant malignancy was associated with the graft survival [39]; however, we analyzed the data to determine only the de novo cancer incidence after KT, so we were unable to examine the association between cancer incidence and graft outcome. In addition, thanks to the European Senior Program in Europe, a systematic research about factors related to the prognosis of KT in elderly people was recently reported [40].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the methods used for screening cancer development as well as social factors such as smoking, alcohol use, and family history could not be reported. Furthermore, there is a recent report that a pretransplant malignancy was associated with the graft survival [39]; however, we analyzed the data to determine only the de novo cancer incidence after KT, so we were unable to examine the association between cancer incidence and graft outcome. In addition, thanks to the European Senior Program in Europe, a systematic research about factors related to the prognosis of KT in elderly people was recently reported [40].…”
Section: Discussionmentioning
confidence: 99%